Item response theory analysis of the Amyotrophic Lateral Sclerosis Functional Rating Scale-Revised in the Pooled Resource Open-Access ALS Clinical Trials Database. Issue 3 (18th May 2016) - Bacci, Elizabeth D.; Staniewska, Dorota; Coyne, Karin S.; Boyer, Stacey; White, Leigh Ann; Zach, Neta; Cedarbaum, Jesse M.; ,
Abstract: Our objective was to examine dimensionality and item-level performance of the Amyotrophic Lateral Sclerosis Functional Rating Scale-Revised (ALSFRS-R) across time using classical and modern test theory approaches. Confirmatory factor analysis (CFA) and Item Response Theory (IRT) analyses were conducted using data from patients with amyotrophic lateral sclerosis (ALS) Pooled Resources Open-Access ALS Clinical Trials (PRO-ACT) database with complete ALSFRS-R data ( n = 888) at three time-points (Time 0, Time 1 (6-months), Time 2 (1-year)). Results demonstrated that in this population of 888 patients, mean age was 54.6 years, 64.4% were male, and 93.7% were Caucasian. The CFA supported a 4* individual-domain structure (bulbar, gross motor, fine motor, and respiratory domains). IRT analysis within each domain revealed misfitting items and overlapping item response category thresholds at all time-points, particularly in the gross motor and respiratory domain items. Results indicate that many of the items of the ALSFRS-R may sub-optimally distinguish among varying levels of disability assessed by each domain, particularly in patients with less severe disability. Measure performance improved across time as patient disability severity increased. In conclusion, modifications to select ALSFRS-R items may improve the instrument's specificity to disability level and sensitivity to treatment effects.